The Mediating Role of Work Discipline on The Effect of Leadership and Work Ethic to Employee Performance in Universitas Advent Indonesia - Malau, Harman; Sitanggang, Juninetenth Keeply F (IJBLE Scientific Publications Community Inc., 2024)
This study aims to find out and analyze the influence of leadership and work ethic on discipline, the influence of discipline on performance, the influence of leadership and work ethic on performance, the influence of leadership on performance through discipline and to find out and analyze the influence of work ethic on performance through employee discipline at Adventist University Indonesia. With the Simple Random Sampling technique, a sample of 104 employees was obtained in this study. Data were collected through questionnaires, interviews and documentation studies. The questionnaire was calculated using the Likert scale unit of measurement, and processed using the path analysis method (path analysis. The results of the study show that Leadership has a positive and significant effect on discipline, Work Ethic has a positive and significant effect on Discipline, Discipline has a positive and significant effect on Performance, Leadership has a positive and significant effect on Performance, Work Ethic has a positive and significant effect on Performance, Leadership has a positive and significant effect on Performance through Discipline, and Work Ethic has a positive and significant effect on Performance through Discipline at Advant University Indonesia which proves that Discipline is an intervening variable in this study.